Forage potential and carrying capacity of Indigofera sp and Pennisetum purpureum. Issue 1 (June 2021) - Saking, N; Ruba, K; Qomariyah, N
Abstract: The purpose of this study was to find out the forage potential and cattle carrying capacity under Indigofera sp and Pennisetum Purpureum forage plants. This study was carried out in Technical Implementation Unit of Livestock Breeding and forage development, Provincial Livestock and Animal Health Services of South Sulawesi Province, Pucak Village, Tompobulu Sub District, Maros Regency, South Sulawesi Province in March 2020. This study used survey method and purposive sampling every 1 m 2 with a sample distance of 30 until 50 m or an average of 40 meters. This study identified forage in the area of Indigofera sp and Pennisetum purpureum. Based on the results, the average forage production in Indogofera sp and Pennisetum purpureum areas was 105, 000 kg ha −1 . The average cattle carrying capacity in Indogofera sp and Pennisetum purpureum areas was 0.14 AU⋅Ha −1 ⋅year −1 . Thus, it can be concluded that the forage potential under the main forage ( Indigofera sp and Pennisetum purpureum ) was very high but had low utilization.